The Critical Success Factor in Implement Occupational Safety and Health (OSHA) - Nurul Huda, Hussain (2009)
This research paper presents the critical success factor in implementing Occupational Safety and Health (OSHA). Occupational Safety and Health (OSHA) is a body to make sure the safety of the employee being protected by the government body known as National Institute of Safety and Health (NIOSH) under the ministry of human resource. However, the study is to identify which factors that influences most in the success of Safety and Health in an organization. It is because there were reported that about 70% of government sector fail to comply with Occupational safety and Health Act (OSHA) 1994. However, safety is big terms that represent the company’s back bone. The weak and strength of safety in an organization will define the strength and weak the organization will be. Furthermore, safety cannot move alone by itself, therefore safety can be implemented if there is two parties make the same approach and responsibilities that enable the safety become more effective. Therefore the objective of this paper is to find out what are the needs to improve the safety in organization.